2015
DOI: 10.1186/s13069-015-0031-z
|View full text |Cite
|
Sign up to set email alerts
|

In vitro reversion of activated primary human hepatic stellate cells

Abstract: BackgroundLiver fibrosis is characterized by the excessive formation and accumulation of matrix proteins as a result of wound healing in the liver. A main event during fibrogenesis is the activation of the liver resident quiescent hepatic stellate cell (qHSC). Recent studies suggest that reversion of the activated HSC (aHSC) phenotype into a quiescent-like phenotype could be a major cellular mechanism underlying fibrosis regression in the liver, thereby offering new therapeutic perspectives for the treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
79
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 59 publications
10
79
0
Order By: Relevance
“…This phenomenon is consistent with the outcome of elegant fate-mapping studies in mice that demonstrated a subset of HSCs are able to revert to a quiescent-like phenotype (Kisseleva et al, 2012) during the resolution of fibrotic injury. HSCs that have been previously activated exhibit a primed phenotype with rapid and robust patterns of reactivation in response to subsequent injury (Kisseleva et al, 2012;Taghdouini et al, 2015). This observation could explain the accelerated fibrogenic features observed in the current study, compared to the clinical setting in which fibrosis can take months or even years to develop.…”
Section: Discussionmentioning
confidence: 64%
“…This phenomenon is consistent with the outcome of elegant fate-mapping studies in mice that demonstrated a subset of HSCs are able to revert to a quiescent-like phenotype (Kisseleva et al, 2012) during the resolution of fibrotic injury. HSCs that have been previously activated exhibit a primed phenotype with rapid and robust patterns of reactivation in response to subsequent injury (Kisseleva et al, 2012;Taghdouini et al, 2015). This observation could explain the accelerated fibrogenic features observed in the current study, compared to the clinical setting in which fibrosis can take months or even years to develop.…”
Section: Discussionmentioning
confidence: 64%
“…As one of saturated fatty acids, PA was found to stimulate inflammasome NLRP3 activation in cultured Kupffer cells [32], but the results in HSCs are contradictory when different HSC lines and various concentrations were used. One study reported that PA at 75 μM led to growth rest and decrease in HSC activation [33], and another study claimed that PA at 100 μM in combination with EGF at 40 ng/mL, FGF at 220 ng/mL, oleic acid at 100 μM, and retinol at 5 μM, had a net effect of reverting HSCs to a quiescent status [34]. Whereas, in the present study, we confirmed that PA at 200 μM elicited HSC activation through the activated inflammasome NLRP3 molecule.…”
Section: Discussionmentioning
confidence: 99%
“…As well, in isolated human HSCs, the results are not consistent. Positive immunostaining for desmin has been observed in primary isolated human HSCs in some studies [23,31,38], while negative immunoreactivity for desmin was reported in others [61,71].…”
Section: Desminmentioning
confidence: 94%
“…The cultured hHSCs produced monocyte chemotactic protein-1 (MCP-1) [45], and responded to TGFb1 with increased PDGFRb [48]. It has been demonstrated that density gradient isolated human HSCs can be reverted to a quiescent-like phenotypes through synergistic action of epidermal growth factor (EGF), fibroblasts growth factor 2 (FGF2), dietary fatty acids (oleic acid, palmitic acid) and retinol, as demonstrated by the abundant presence of retinyl ester-positive intra-cytoplasmic lipid droplets, and low expression levels of activation markers [31].…”
Section: Liver Tissue Explantsmentioning
confidence: 99%
See 1 more Smart Citation